Optimalisasi Penjatuhan Hukuman Akibat Indisipliner Kerja Pegawai Negeri Sipil - Fathur Rauzi (Faculty of Law Universitas Muhamadiyah Yogyakarta, 2022)
Discipline is the ability of Civil Servants to comply with obligations and avoid prohibitions regulated in the applicable laws and regulations. The purpose of this study was to determine the benchmarks for imposing disciplinary penalties in Article 4 letter f according to the level of discipline and type of discipline. The method used in this study uses a normative-empirical approach, namely looking for data in the literature in which there are laws and regulations which are further elaborated with an empirical approach, namely the working of these norms in an institution, especially Government Regulation Number 94 of 2021 concerning Civil Servant Discipline. In this study, it was found that the imposition of disciplinary penalties for perpetrators who committed violations according to the author was not optimal because of the low understanding of the applicable laws and regulations and not optimal supervision from direct superiors. Disciplinary law against Civil Servants who violates Article 4 letter f in Government Regulation Number 94 of 2021 concerning Civil Servant Discipline is divided into three categories: 1) the category of light discipline does not come to work without a valid reason up to ten working days for a year , 2) category of moderate punishment violation without the principle of cooperation with twenty thirty days, 3) category of violation of law without the principle of cooperation as a whole 21 (twenty one) to 28 (twenty eight) working days and or continuously for 10 (ten) working days for a year